A Serrate-expressing signaling center controls Drosophila hematopoiesis. - Lebestky, T.; Jung, S.H.; Banerjee, U. (Genes & Development, 2003)
The differentiation of Drosophila blood cells relies on a functional hierarchy between the GATA protein, Serpent (Srp), and multiple lineage-specific transcription factors, such as the AML1-like protein, Lozenge (Lz). Two major branches of Drosophila hematopoiesis give rise to plasmatocytes/macrophages and crystal cells. Serrate signaling through the Notch pathway is critical in the regulation of Lz expression and the specification of crystal cell precursors, thus providing a key distinction between the two lineages. The expression of Serrate marks a discrete cluster of cells in the lymph gland, a signaling center, with functional similarities to stromal signaling in mammalian hematopoiesis.